Blunted perception of neural respiratory drive and breathlessness in patients with cystic fibrosis. Issue 1 (5th March 2016) - Reilly, Charles C.; Jolley, Caroline J.; Elston, Caroline; Moxham, John; Rafferty, Gerrard F.
The electromyogram recorded from the diaphragm (EMGdi ) and parasternal intercostal muscle using surface electrodes (sEMGpara ) provides a measure of neural respiratory drive (NRD), the magnitude of which reflects lung disease severity in stable cystic fibrosis. The aim of this study was to explore perception of NRD and breathlessness in both healthy individuals and patients with cystic fibrosis. Given chronic respiratory loading and increased NRD in cystic fibrosis, often in the absence of breathlessness at rest, we hypothesised that patients with cystic fibrosis would be able to tolerate higher levels of NRD for a given level of breathlessness compared to healthy individuals during exercise. 15 cystic fibrosis patients (mean forced expiratory volume in 1 s (FEV1 ) 53.5% predicted) and 15 age-matched, healthy controls were studied. Spirometry was measured in all subjects and lung volumes measured in the cystic fibrosis patients. EMGdi and sEMGpara were recorded at rest and during incremental cycle exercise to exhaustion and expressed as a percentage of maximum (% max) obtained from maximum respiratory manoeuvres. Borg breathlessness scores were recorded at rest and during each minute of exercise. EMGdi % max and sEMGpara % max and associated Borg breathlessness scores differed significantly between healthy subjects and cystic fibrosis patients at rest and during exercise. The relationship between EMGdi % max and sEMGpara % max and Borg score was shifted to the right in the cystic fibrosis patients, such that at comparable levels of EMGdi % max and sEMGpara % max the cystic fibrosis patients reported significantly lower Borg breathlessness scores compared to the healthy individuals. At Borg score 1 (clinically significant increase in breathlessness from baseline) corresponding levels of EMGdi % max (20.2±12% versus 32.15±15%, p=0.02) and sEMGpara % max (18.9±8% versus 29.2±15%, p=0.04) were lower in the healthy individuals compared to the cystic fibrosis patients. In the cystic fibrosis patients EMGdi % max at Borg score 1 was related to the degree of airways obstruction (FEV1 ) (r=−0.664, p=0.007) and hyperinflation (residual volume/total lung capacity) (r=0.710, p=0.03). This relationship was not observed for sEMGpara % max. These data suggest that compared to healthy individuals, patients with cystic fibrosis can tolerate much higher levels of NRD before increases in breathlessness from baseline become clinically significant. EMGdi % max and sEMGpara % max provide physiological tools with which to elucidate factors underlying inter-individual differences in breathlessness perception. Patients with CF can tolerate higher levels of NRD before breathlessness becomes clinically significant http://ow.ly/Xp2q3